?TOXICOLOGICAL STUDIES OF HERBAL BEVERAGE AND SEEDS EXTRACT OF HIBISCUS SABDARIFFA L. (ROSELLE) (Biological Sciences - PJSIR, 1996)
Toxicological effects of herbal dririk prepared from exotic plant, Hibiscus sabdariffa L. (Roselle) were studied on albino miceand rats. For this purpose different doses of the drink were administered orally to different groups of test ani- mals which were kept under observation for a period of three months. The roselle seeds extract was also administered by the same method and tested on the animals. After autopsy, the histopathological examination of liver and kidneys of the treated animals showed on cytotoxic effects.